Serotypes, Virulence-Associated Factors, and Antimicrobial Resistance of Streptococcus suis Isolates Recovered From Sick and Healthy Pigs Determined by Whole-Genome Sequencing - Aradanas, Maverick; Poljak, Zvonimir; Fittipaldi, Nahuel; Ricker, Nicole; Farzan, Abdolvahab (Frontiers in Veterinary Science, 2021)
Streptococcus suis is ubiquitous in swine and yet only a small percentage of pigs become clinically ill. The objective of this study was to describe the distribution of serotypes, virulence-associated factor (VAF) and antimicrobial resistance (AMR) genes in S. suis isolates recovered from systemic (blood, meninges, spleen and lymph node) and non-systemic (tonsil, nasal cavities, ileum and rectum) sites of sick and healthy pigs using whole genome sequencing (WGS). In total, 273 S. suis isolates recovered from 112 pigs (47 isolates from systemic and 136 from non-systemic sites of 65 sick pigs; 90 isolates from non-systemic sites of 47 healthy pigs) on 17 Ontario farms were subjected to WGS. Using in silico typing, 21 serotypes were identified with serotypes 9 (13.9%) and 2 (8.4%) as the most frequent serotypes, while 53 (19.4%) isolates remained untypable. The relative frequency of VAF genes in isolates from systemic (Kruskal-Wallis (KWT), p < 0.001) and non-systemic (KWT, p < 0.001) sites in sick pigs was higher compared to isolates from non-systemic sites in healthy pigs. Although many VAF genes were abundant in all isolates, three genes including dltA (Fisher’s test (FT), p < 0.001), luxS (FT, p = 0.01) and troA (FT, p = 0.02) were more prevalent in isolates recovered from systemic sites compared to non-systemic sites of pigs. Among the isolates, 98% had at least one AMR gene and 79% had genes associated with at least four drug classes. The most frequently detected AMR genes were tetO conferring resistance to tetracycline, and ermB conferring resistance to macrolide, lincosamide and streptogramin (MLS). The wide distribution of VAFs genes in S. suis isolates in this study suggests that other host and environmental factors may contribute to S. suis disease development.